REGULATION TO MAKE USERS OF TOBACCO INELIGIBLE FOR EMPLOYMENT AS NEW FLORIDA FIRE FIGHTERS - GERACE,TA (Tufts Archival Research Center, 2007)
Duplicate; Commentary on the proposed regulation against hiring of tobacco users as fire fighters in Florida. Discusses the scientific merit of the regulation, as well as precedents set for other health conditions in Florida and for tobacco use in other locales. Explains the political rationale and provides names of supportive fire fighter groups as well as other endorsers.